2017
DOI: 10.1155/2017/8569328
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro/In Silico Study on the Role of Doubling Time Heterogeneity among Primary Glioblastoma Cell Lines

Abstract: The application of accurate cancer predictive algorithms validated with experimental data is a field concerning both basic researchers and clinicians, especially regarding a highly aggressive form of cancer, such as Glioblastoma. In an aim to enhance prediction accuracy in realistic patient-specific environments, accounting for both inter- and intratumoral heterogeneity, we use patient-derived Glioblastoma cells from different patients. We focus on cell proliferation using in vitro experiments to estimate cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…Aliquots of zero stage, as well as various passages of in vitro cell tissue were cryopreserved, nucleic acids were extracted for further analysis and immunohistopathology was performed. The average doubling time intervals were estimated following a simple protocol in adherent cultures for both the established primary GB culture and the U87MG cell line which was used as a control (as described in 64 ). All possible steps and procedures have been approved by the Institutional Ethical Committees.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliquots of zero stage, as well as various passages of in vitro cell tissue were cryopreserved, nucleic acids were extracted for further analysis and immunohistopathology was performed. The average doubling time intervals were estimated following a simple protocol in adherent cultures for both the established primary GB culture and the U87MG cell line which was used as a control (as described in 64 ). All possible steps and procedures have been approved by the Institutional Ethical Committees.…”
Section: Methodsmentioning
confidence: 99%
“…If a quiescent cell finds an empty space, it immediately proliferates. The neighbourhood chosen for the proliferation was the Moore neighbourhood of size r equal to 2 (for more details also see 64 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our study all treatments were performed following the specifications made by the vendor, henceforth all dose analyses were based upon these terms [13]. Table 1 Characteristics of the 7 glioblastoma patients: Tumor localization in the patient; study arm A or B; treatment technique; skin high dose area (surface dose > 70% of the prescribed dose within or up to 6 mm below the skin on a scalp area are of > 50 cm 2 Note: doses are given as relative doses normalized to the prescribed dose; five adjacent scalp + calvaria layers were defined as tissue slices of 2 mm thickness below the surface of the scalp in a depth of 0-2 mm, 2-4 mm, 4-6 mm, 6-8 mm and 8-10 mm; D95: minimum dose in 95% most exposed voxel of the structure; D2: minimum dose in the 2% most exposed voxels of the structure Previous film dosimetry measurements showed that transducer arrays may increase the dose build-up to 82, 88 and 98% of the maximal dose build-up per beam at a depth of 0.4 mm and incident beam angles on the surface of 90°, 45°and 10° [29]. In the present study, the maximal voxel-wise dose difference with and without onlying transducer arrays ranged from 24 to 29% of the prescribed dose observed in the superficial 2 mm of the scalp outside the 1 cm 2 with the largest dose differences.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma (World Health Organization grade IV glioma [1]) is a rapidly proliferating tumor [2,3]. Despite a trimodal approach, overall survival and progression free survival rates remain low [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the early stages of metastatic cancer cell invasion, the length scale L is taken to be 1 cm but could be in the range of 0.1 to 1 cm. The residence time τ is taken to be 32 h, which is a representative average in vitro doubling time for the well-established human cancer cell lines of A549 lung carcinoma cells, U87MG glioma cells, and MCF-7 and MDA-MB 231 breast cancer cells [55][56][57][58]. The diffusion coefficient of the cancer cell D c has been previously determined in an experiment of cell movement by [59].…”
Section: Nondimensionalization and Parameter Valuesmentioning
confidence: 99%